2014
DOI: 10.1111/spc3.12123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations in Their Social Context: Distance Regulates Consistency and Context Dependence

Abstract: When and why do people's likes and dislikes flexibly tune to the current context, and when do they remain consistent? Ideas about flexibility and consistency have permeated the attitude literature throughout its history. Building on the notion that both flexibility and consistency in evaluative responding can be highly functional as well as highly social, this paper considers the role of distance in guiding people's evaluations to incorporate specific and individualized information that helps immerse them in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
1
22
1
Order By: Relevance
“…This brokering of evidence may help each party become more aware of the other's needs and ultimately shape the healthpromoting activities policy influencers choose to undertake in their organizations [75]. Moreover, research shows that knowledge brokers can help to mitigate the influence of ideological belief on policy support by addressing policy influencers' particular context [33,34]. Knowing the KAB of particular sectors of policy influencers could be instrumental in tailoring messages to address knowledge gaps and foster positive attitudes toward cancer prevention policy.…”
Section: Implications For Policy Advocacy and Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…This brokering of evidence may help each party become more aware of the other's needs and ultimately shape the healthpromoting activities policy influencers choose to undertake in their organizations [75]. Moreover, research shows that knowledge brokers can help to mitigate the influence of ideological belief on policy support by addressing policy influencers' particular context [33,34]. Knowing the KAB of particular sectors of policy influencers could be instrumental in tailoring messages to address knowledge gaps and foster positive attitudes toward cancer prevention policy.…”
Section: Implications For Policy Advocacy and Implementationmentioning
confidence: 99%
“…Political commitment to implementing policies for cancer prevention thus requires knowledge of the issue as well as evidence of policy effectiveness and sustained public benefit. Attitude, as positive or negative evaluation of healthy public policy, is central to the issue of political commitment [26,33]. Cohen [34] demonstrated experimentally that attitudes serve the social function of self-identification with a group, by showing that research participants' attitude toward hypothetical policy proposals shifted according to the political ideology attributed to them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are contexts in which individuals are more influenced by anecdotal information, even to the disregard of aggregate base rates (i.e., base-rate neglect; Kahneman & Tversky, 1973), in other contexts, individuals may rely more on aggregate, statistical information (e.g., Amazon star ratings; Ledgerwood, Wakslak, & Wang, 2010). Importantly, researchers have identified that the influence of these two sources of information in decision-making may vary with construal (Ledgerwood, Trope, & Chaiken, 2010;Ledgerwood, Wakslak, & Wang, 2010; for a review, see Ledgerwood, 2014).…”
Section: Social Influencementioning
confidence: 99%
“…In their 2015 metaanalysis, Soderberg and colleagues synthesized 125 studies with 310 effect sizes estimating the effect of psychological distance on abstraction (Soderberg, Callahan, Kochersberger, Amit, & Ledgerwood, 2015), and the literature has only grown since. Researchers have also hypothesized and tested a wide variety of implications that the effect of psychological distance on abstraction might have for downstream outcomes in different topic areas, from counterfactual thinking to mimicry and from self-complexity to health behavior (e.g., Choi, Park, & Oh, 2012;Genschow, Hansen, Wanke, & Trope, 2019;Ledgerwood, 2014;Rim & Summervile, 2014;Wakslak, Nussbaum, Liberman, & Trope, 2008; see Soderberg et al, 2015, for a meta-analytic synthesis of 426 effect sizes across 179 studies testing the effects of psychological distance on various downstream consequences of abstraction).…”
mentioning
confidence: 99%